Submission Instructions - Rodrigues Junior, Otavio Luiz (Revista de Direito Civil Contemporâneo, 2020)
The Journal of Contemporary Private Law, ISSN 2358-1433, published quarterly by Editora Revista dos Tribunais, in Brazil, invites academics and researchers to submit unpublished papers for its first issue of 2015, in the following areas: [...]